Analisis Metode Penentuan Biaya Produksi Pada PT. Sinergi Gula Nusantara Pabrik Gula Camming Kabupaten Bone - Catriani; Muhammad Yamin; Masyhuri (Journal of Mandalika Literature, 2025)
This study aims to analyze the effectiveness of the full costing method in describing production costs and identifying the advantages and disadvantages of implementing the full costing method at PT. Sinergi Gula Nusantara Camming Sugar Factory, Bone Regency. This company is one of the sugar factories engaged in the agribusiness sector, with a production process that includes processing sugar cane into granulated sugar that is ready for consumption. This study uses a descriptive quantitative approach, with data collection techniques in the form of observation, interviews with the company and documentation of financial reports for the period 2023 - 2024. The results of the study indicate that the application of the full costing method in describing production costs at PT. Sinergi Gula Nusantara Camming Sugar Factory, Bone Regency is still less effective. This is because there are still several fixed cost components that are not allocated, such as depreciation costs for heavy equipment and depreciation costs for plant transportation equipment. In addition, the Camming Sugar Factory does not group in detail whether these costs are included in the categories of raw material costs, direct labor costs and factory overhead costs and this method tends to produce higher production costs, thus impacting the competitiveness of product prices in the market. Based on these findings, it is recommended that Camming Sugar Factory make improvements in the cost recording and reporting system that clearly separates the components of raw material costs, direct labor costs and factory overhead costs and records each cost component in detail so that the company can manage costs accurately and competitively